Local Wisdom in Housing and Settlement Planning: A Case Study of Sudiroprajan Chinatown, Surakarta - Suminar, Lintang; Astuti, Winny; Sunjaya, Nyimas Indri; Kusumaputri, Azzahra Nugrarizky; Margareta, Lauren Adellia; Pamungkas, Paundra Bintang (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
Local wisdom is essential in urban development planning by bringing cultural values. Local wisdom in housing and settlements forms special characteristics both in spatial and social aspects. Chinatown is a form of residential area created by Chinese community groups. Sudiroprajan Chinatown Village is the center of Chinese settlement which is also located in the economic center area of Surakarta City. The method used in this research is qualitative with literature study, observation, description and analysis of settlement character based on physical and non-physical characteristics. Chinatown Village has a linear pattern following the road and is influenced by feng shui in arranging the interior and exterior of housing. Most residents in Sudiroprajan Chinatown Village work in the trade and services sector, namely by opening businesses in house buildings or at Pasar Gede. The temple is also the worship centre for Chinese residents in Chinatown Village. The local wisdom found in Chinatown Village influences other activities, such as the emergence of economic activities and cultural tourism. This shows that local wisdom influences the character and condition of settlements physically and non-physically.